POPULIST DISCOURSE ON POLITICAL REPRESENTATION: A CASE STUDY OF ANTI-ESTABLISHMENT ORGANIZATIONS IN LITHUANIA - Stašienė, Jogilė (Baltic Journal of Political Science, 2017)
Today’s party democracy crisis coincides with an increasing influence of populist political actors. This article— prompted by notions of populist understandings of politics as expressions of the people’s will and of the populist idea of an antagonism between the people and the elite—explores whether populism and party democracies are compatible. Assertions, that populism contradicts party democracies, should rest on research of populist understandings of political representation. This case study, of the populist discourse of Lithuania’s anti-establishment organizations, fills this research gap in the literature on populism’s compatibility with party democracies. The qualitative analysis of this case study focuses on how political representation is perceived and presented. The study provides new insights for theoretical debate on the compatibility of populism and party democracy and also presents a nuanced picture of populist perceptions of political representation.